Dampak Persepsi Tanggung Jawab Sosial Perusahaan terhadap Manajemen Perpajakan (Tax Planning) - M Khoiru Rusydi (Jurnal Akuntansi dan Bisnis, 2009)
Growth of Corporate Social Responsibility (CSR) at this time in Indonesia more onward than before all period, this matter seen to the number of medias printing and electronic publicizing activity of CSR in Indonesia. This awareness is positive for development of Indonesia, although still many oppositions between mandatory and voluntary in implementation of CSR. This Opposition was more effected the difference of corporation perception to CSR itself as well as ethic principles have business, according to research of PIRAC there are 5 ( five perception) corporation to CSR, where each bringing impact at policy of management specially at tax planning encumbering of CSR expense. Corporation running CSR, but the behavior of tax planning of not yet as according to principle of CSR specially ethical principle, will affect at corporation sustainability, for challenging effect of local community surround company, and action effect of tax planning which enter in doing an injustice.